Perception and production of english syllable-final nasals by brazilian learners - Kluge, Denise Cristina (2004)
Dissertação (Mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-graduação em Letras-Inglês e Literatura Correspondente